Response of Eggplant (Solanum melongena) to Diluted Seawater Irrigation - Marian S. Dela Cruz; Almoguera, Laurence (Universitas Negeri Semarang, 2025)
The rapid growth of the global population is driving an increasing demand for fresh water, particularly for domestic, industrial, and agricultural use. As freshwater resources become scarcer, exploring alternative water sources for agriculture is imperative to ensure food security. Therefore, this research was conducted to determine whether diluted seawater would impact the growth and productivity of eggplant. The effects of irrigation water with five different salt levels—0, 0.5%, 1.0%, 1.5%, and 2.0% %—were observed on eggplants (Calixto F1) that were grown in pots for three months. Response variables evaluated included plant height increment, leaf development, stem diameter increase, number of fruits harvested, and unit weight of fruits. The physicochemical properties of the irrigation water and growing media were also tested. The findings revealed that while the overall growth parameters were not significantly affected by the varying salt levels (p>0.05), a notable increase in fruit yield was observed at a 0.5% salinity level. This suggests that a minimal salt concentration in irrigation water can enhance eggplant productivity without compromising plant health. With these findings, this research presents an innovative approach to using diluted seawater as an irrigation strategy for eggplant cultivation. This approach offers a sustainable solution for agriculture in coastal and arid regions where freshwater is limited.